Futures possibilities for education in the face of global challenges: regenerative design as a driver for change - Murgatroyd, Stephen (REVISTA PARAGUAYA DE EDUCACIÓN A DISTANCIA (REPED), 2023)
Anticipatory studies suggest that our current school system is no longer fit for purpose. Not only is it failing in its human capital mission, but it is also failing in its core mission of enabling active and engaged citizenship. It is time for a major rethink. This paper suggest a framework for such a rethink – regenerative design for sustainable development. The underlying idea of this approach are outlined together with eight principles which should inform this work.